Platinum-Free Electrocatalyst for Oxygen Reduction Reaction Derived from the Direct Pyrolysis of Waste Watermelon Peels - Matibag, Via Kryshl Ranillo; Geronimo, Hannah Grace Defeo; Garcia, Jonyl Lomigo; Tongol, Bernard John Vallejos (International Journal of Integrated Engineering, 2019)
Carbon-based nanomaterials derived from the pyrolysis of heteroatom-containing carbonaceous precursor was shown to exhibit significant electrocatalytic activity towards oxygen reduction reaction (ORR). Biomass from agricultural waste could be seen as possible low-cost precursor for the preparation of carbon-based ORR electrocatalysts. In this study, watermelon peels (WP) were directly pyrolyzed under N2 atmosphere to produce novel carbon-based ORR electrocatalysts. WP were oven-dried and pulverized using a mechanical grinder to produce WP powder. A weighed amount of the resulting powder was then transferred into a ceramic boat and inside a quartz tube furnace. The WP powder was pyrolyzed from room temperature to pyrolysis temperature T at a rate of 5 °C/min under N2 atmosphere. The temperature was held at T for an hour, followed by natural cooling back to room temperature. The pyrolysis temperature was optimized, with T = 800 °C, 900 °C, and 1000 °C. The resulting pyrolysis products were characterized using cyclic voltammetry (CV), rotating disc electrode voltammetry (RDE), and scanning electron microscopy-energy dispersive x-ray spectroscopy (SEM-EDX). CV revealed that WP pyrolyzed at 1000 °C gave the most positive onset potential (Eonset = 0.40 V) and highest current density (j = 10.79 mA/cm2), compared to those pyrolyzed at 800 °C (Eonset = 0.30 V; j = 2.047 mA/cm2) and 900 °C (Eonset = 0.30 V; j = 3.494 mA/cm2). Levich analysis from RDE data showed that the electrocatalysts prepared at 1000 °C proceeded closest to the ideal four-electron route, compared to those prepared at 800 °C and 900 °C. SEM-EDX analysis showed the changes WP underwent in terms of surface morphology and elemental composition, which are then correlated with the apparent electrocatalytic activities of pyrolyzed WP. These findings present the feasibility of using WP as low-cost precursor for ORR electrocatalysts, which could be utilized in fuel cells.